Mango stone-derived activated carbon with high sulfur loading as a cathode material for lithium–sulfur batteries. Issue 46 (21st April 2016) - Zhang, Songtao; Zheng, Mingbo; Lin, Zixia; Zang, Rui; Huang, Qingli; Xue, Huaiguo; Cao, Jieming; Pang, Huan
Abstract : A mango stone-derived activated carbon/sulfur composite cathode with a high sulfur loading of 71 wt% for long cycle-life Li–S batteries. Abstract : A set of mango stone (MS)-derived activated carbons with tunable pore structure parameters have been synthesized via a KOH activation procedure. The maximum specific surface area of 3334 m 2 g −1 and pore volume of 2.17 cm 3 g −1 are obtained for the material which is pre-carbonized at 500 °C and treated with a KOH/char mass ratio of 4 (a-MSs-500-4). Given the large pore volume of the resultant a-MSs-500-4 activated carbon, a high sulfur loading of up to 71 wt% can be achieved (a-MSs-500-4/71). When applied in a lithium–sulfur battery, the a-MSs-500-4/71 composite cathode exhibits 64% capacity retention over 500 cycles at 800 mA g −1 and 45% capacity retention over 1000 cycles at 1600 mA g −1, indicating excellent long-term cycling performance. Moreover, after 1 wt% LiNO3 is introduced as the electrolyte additive, the average coulombic efficiency of the electrode is as high as approximately 99%.